How do mandatory clawback provisions affect firm value? Evidence from the SEC’s enforcement actions - Li, Wen (2014)
I examine how the SEC’s enforcement actions on mandatory clawback provisions affect shareholder wealth. I hypothesize that enforcing clawback provisions is likely to be value-increasing for firms with a higher likelihood of restating earnings, value-decreasing for firms with a higher likelihood of engaging in real earnings management and value-decreasing for firms with more risk-averse managers. My results support my hypotheses and suggest that the mandatory clawback provisions may create value for some firms but it may destroy value for others. My study provides important implications for the valuation consequences of the mandatory adoption of clawback provisions under the Dodd-Frank Act.